Identifying forward market scopes through value chain analysis: a study on dairy and maize sub-sectors - Riaz, Ahammed (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.